Oxytocin massage and clary sage aromatherapy on lactation and uterine recovery - Rahmadini Faricha Hakim; Dyan Permata Rachim; Hindun Mila Hudzaifah; Ulfa Farrah Lisa; Dina Taufia; Fathiya Ilma Shabrina (Intelektual Pustaka Media Utama, 2026)
The postpartum period is a critical phase in maternal health, during which inadequate lactation and delayed uterine involution may contribute to an increased risk of complications. This study aimed to determine the effectiveness of combined oxytocin massage and clary sage aromatherapy on lactation and uterine involution in women during the postpartum period. A quasi experimental study was conducted among 30 participants (15 controls; 15 intervention). In the control group, mean breast milk volume increased from 32.00 ± 14.74 mL to 105.33 ± 18.07 mL (Δ = 73.33 ± 17.29; p < 0.001). In the intervention group, it increased from 37.00 ± 24.04 mL to 98.33 ± 40.39 mL (Δ = 61.33 ± 36.62; p<0.001), with no significant intergroup difference (p = 0.265). However, uterine involution differed significantly between groups (Mann-Whitney U = 43.000, Z = -2.932, p = 0.003). The combined intervention may serve as a complementary strategy to enhance uterine recovery, although its effect on breast milk production was not statistically superior to standard care.